Major chemical elements concentration in metalliferous sediments of the southwest Pacific - David S Cronan (PANGAEA, 2022)
Chemical elements in the samples analysed were determined by atomic absorption spectrophotometry after completely dissolving the samples in a mixture of hydrofluoric, nitric and perchloric acids. The chemical data were corrected for calcium interference, and the precision of the analyses was better than ± 4% at 2 s.d. for Ca, Al, Mn, Fe and Cu, ±5% for Zn, ± 14% for Ni and ±25% for Pb. Accuracy was checked by the analysis of several international standards. Samples are distributed irregularly throughout the southwest Pacific region, the major sampling being concentrated along the island arc-trench systems, and in the North and South Fiji Basins. In addition, a number of samples from near New Zealand have been included.